Impact Evaluation to Inform and Transform Investments in Transport and ICT - Vandycke, Nancy; Legovini, Arianna; Liaplina, Aleksandra; Di Maro, Vincenzo (World Bank Group, Washington, DC, 2015)
A new World Bank initiative, ‘Impact Evaluation (IE) - connect for impact,’ aims to radically transform and better inform the way that transport and information and communications technology (ICT) projects are designed and implemented. Although multilateral lending to this key strategic sector comprises 29 percent of all global assistance, only 0.4 percent of impact evaluations have had transport as a subject. This initiative aims to fill the gap and bring high quality and valuable feedback to projects, improving design, enabling mid-course corrections, and informing ex-post evaluations. For the first time, this initiative will offer a systematic sector approach to generating concrete evidence of what works, what does not, where, when and why. It will greatly increase the impact and value add of investments in transport and ICT projects, which is especially important given global trends toward increasing urbanization, with 70 percent of the world’s population expected to live in cities by 2050.